An Analysis of Principals’ Digital Literacy Capabilities as Instructional Leaders in Indonesia - Dwiniasih, Dwiniasih; Jaja, Jaja; Raharjo, Jajo Firman (International Journal of Applied Sciences and Smart Technologies, 2024)
The role of principals as instructional leaders requires them to continuously improve their skills in designing and implementing 21st-century learning. This involves developing their digital literacy capabilities as part of technology integration. This research is a case study that aims to analyze the digital literacy capabilities of principals in Kuningan and Cirebon, Indonesia, as instructional leaders in designing and implementing 21st-century learning. The participants of this study were 20 elementary school headmasters. To collect the data, the authors used a teacher observation checklist, with the observer being the teacher in charge of the training. The results of this study showed that the headmasters, as supervisors and instructional leaders, had strong digital literacy capabilities. They were able to easily use technology, and the applications were clear and understandable to them. Furthermore, the participants found it easy to become skilled with the system, learn to operate it, and interact with it. They also showed high mental effort, required much care and attention, and found it easy to navigate and remember how to perform tasks with the system. Overall, this study highlights the importance of developing digital literacy capabilities among instructional leaders, particularly in the context of 21st-century learning. The study provides insights for educators and policymakers on how to support principals in improving their digital literacy capabilities to serve as effective instructional leaders in the digital age. Keywords: Digital Literacy, instructional leaders, principals’ capabilities